The Effectiveness of Distance Learning Using the NHT Type Cooperative Learning Model (Number Head Together) - Ummiati Rahman; Marlinda R. Pagayang; Sutarsi Suhaeb (Ceddi Journal of Education, 2023)
This study aims to (1) determine the learning process using the google meeting application in the Electronic Measuring Instruments and Measurement Systems course with the NHT type cooperative model, (2) determine the level of effectiveness of student learning outcomes using the google meeting application in the Measuring Instruments and Measurement Systems course Electronics with NHT type cooperative models. This type of research is PTK (Classroom Action Research) Participants. The subjects in this study were students majoring in Electronic Engineering Education (S1) Class 02, Faculty of Engineering, Universitas Negeri Makassar with 32 respondents. Data analysis techniques used in descriptive analysis research. The results of the study reveal that distance learning using the Google meeting application is effective and improves student learning outcomes. The pretest in cycle 1 obtained an average N gain in learning outcomes of 0.31, which means that no student reached the minimum standard of completeness (KKM), while in the posttest stage, 15 students met the minimum standard of completeness. Furthermore, classically obtained a posttest value of 46% in cycle 1 and there was an increase in cycle 2 with an average value of N learning gain of 0.70. In cycle 2, 6 students obtained pretest scores reaching KKM and 29 students achieving KKM on the posttest with a classical completeness percentage of 90%.